2004
DOI: 10.1023/b:ijtp.0000049022.58541.34
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological Particle Creation and Dynamical Casimir Effect

Abstract: In this paper we have considered the particle creation in the spatially closed Robertson-Walker space-time. We considered a real massive scalar field which conformally coupled to the Robertson-Walker background. With the dependence of the scale factor on time, the case under consideration is a dynamical Casimir effect with moving boundaries. *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…III, the spacetime was supposed to play the role of a thermal reservoir such that together the mode pairs constitute a closed system as spacetime is expanding. This situation is similar to the second law of phenomenological non-equilibrium thermodynamics [47] and therefore can be modeled with Equation (40). We note that this model provides interesting insight into the notion of the entropy production.…”
Section: Entropy Productionmentioning
confidence: 62%
See 1 more Smart Citation
“…III, the spacetime was supposed to play the role of a thermal reservoir such that together the mode pairs constitute a closed system as spacetime is expanding. This situation is similar to the second law of phenomenological non-equilibrium thermodynamics [47] and therefore can be modeled with Equation (40). We note that this model provides interesting insight into the notion of the entropy production.…”
Section: Entropy Productionmentioning
confidence: 62%
“…We notice that the form of scale factor Equation (7) is a generalisation of some particular cosmological models, found in literature [39][40][41]. With particular choices of parameters a, b and c we get some well-known models such as radiation dominated universe, which is a case with a = b = 0, c = gives rise to the model discussed in [41].…”
Section: Interpretation Of Resultsmentioning
confidence: 77%
“…The essential difference between our calculations and that presented in [1] is that this author does not take into account the degeneracy factor (l + 1)…”
Section: Discussionmentioning
confidence: 86%
“…The particle creation in a 1 + 1 spatially closed Robertson-Walker space-time was investigated in [2,5]. The 3 + 1 version of this problem has been investigated in a recent work [1] [9]. However, when generalizing the 1+1 solution to the 3+1 one, this author missed a degeneracy factor leading to an incomplete answer for the total number of particles created as well as the corresponding total energy.…”
Section: Introductionmentioning
confidence: 99%
“…In a 1 + 1 spatially closed Robertson-Walker spacetime, this subject was investigated by N.D. Birell and P.C. Davis [5], while the particle creation for a massive scalar field conformally coupled to a spatially closed Robertson-Walker spacetime was discussed in [6], and revisited recently in [7]. Some authors have shown that the amount of particle production in an arbitrary cosmological background can be determined using only the latetime positive frequency modes alone [8].…”
Section: Introductionmentioning
confidence: 99%